METALLOCENE BIS(AZA-CROWN ETHER) LIGANDS AND RELATED-COMPOUNDS - THEIR SYNTHESES, COORDINATION CHEMISTRY, AND ELECTROCHEMICAL PROPERTIES - Beer, P; Keefe, A; Sikanyika, H; Blackburn, C; Mcaleer, J (1990)
The syntheses of new ferrocene and ruthenocene bis(aza-crown ethers) (11)-(14) containing amide bond linkages between the metallocene redox centre and aza-15-crown-5 (1,4,7,10-tetraoxa-13-azacyclopentadecane) and aza-18-crown-6 (1,4,7,10,13-pentaoxa-16-azacyclo-octadecane) are described. Variable-temperature 13C n.m.r. studies on these compounds reveal a common intramolecular dynamic process involving rotation about the N-CO bond whose energy barrier to rotation is cation (Na+ or Li+) dependent. The sodium cation forms 1:2 stoicheiometric complexes with the ferrocene bis(aza-crown ethers), whereas potassium produces a 1:1 intramolecular sandwich complex with the former and a 1:2 complex with the latter. Electrochemical investigations reveal that binding of Na+ and K+ guest cations at the respective aza-crown ether co-ordinating sites results in shifts of the ferrocene oxidation wave to more positive potentials. Lithium produces analogous electrochemical effects with these two compounds, however 13C n.m.r. results suggest this cation exclusively co-ordinates to the respective amide carbonyl oxygen donor atoms. This rationalisation is supported by 'model' ferrocene bis(tertiary amide) derivatives which exhibit redox-responsive behaviour to Li+ while being electrochemically insensitive to Na+ and K+.